Best Management Practices (BMPs): Perimeter Borders - Kati W. Migliaccio; Brian Boman; Jemy Hinton; Kevin Hancock (EDIS)
AE439, a 2-page illustrated fact sheet by Kati W. Migliaccio, Brian Boman, Jemy Hinton, and Kevin Hancock, describes perimeter borders used in agricultural production systems in Florida, their benefits and maintenance. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2009.